2020
DOI: 10.1155/2020/1693730
|View full text |Cite
|
Sign up to set email alerts
|

Expression of AIM2 in Rheumatoid Arthritis and Its Role on Fibroblast-Like Synoviocytes

Abstract: Objectives. To determine differences in AIM2 inflammasome expression levels between rheumatoid arthritis (RA) and osteoarthritis (OA) and to investigate the role of AIM2 in RA fibroblast-like synoviocytes (RA-FLS). Methods. Serum AIM2 levels among health controls (HC, n = 20 ), OA ( n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…The H scores, a semiquantitative immunohistochemical parameter [88], for AIM2 and IL-1β correlated with ESR and CRP levels in patients with RA. Moreover, RNA silencing of AIM2 expression inhibited FLS proliferation [89]. Thus, the AIM2 inflammasome pathway in FLS may be involved in the pathogenesis of RA and may be a therapeutic target.…”
Section: Aim2mentioning
confidence: 97%
“…The H scores, a semiquantitative immunohistochemical parameter [88], for AIM2 and IL-1β correlated with ESR and CRP levels in patients with RA. Moreover, RNA silencing of AIM2 expression inhibited FLS proliferation [89]. Thus, the AIM2 inflammasome pathway in FLS may be involved in the pathogenesis of RA and may be a therapeutic target.…”
Section: Aim2mentioning
confidence: 97%
“… 20 On the contrary, an independent study reported high soluble levels of ASC (apoptosis-associated speck-like protein containing a CARD), caspase-1, and IL-1β in OA patients compared with healthy blood donors; however, its consequence on OA phenotype was not discussed. 48 Soluble factors associated with inflammasome activation have also been observed locally. Synovial fluid from temporomandibular OA patients showed high concentrations of NLRP3, caspase-1, IL-1β, and IL-18, suggesting these molecules initiate degenerative processes in situ.…”
Section: Pathological Mechanisms Driving Inflammasome Activation In Oamentioning
confidence: 99%
“…More importantly, it was reported that AIM2 was increased in RA synovium compared to osteoarthritis (OA) patients. In addition, AIM2 knockdown suppresses the proliferation of RA FLSs but not cell migration and apoptosis ( Chen et al, 2020 ). Herein, we observed some different results.…”
Section: Discussionmentioning
confidence: 99%